Synthesis, structure, and anion binding of functional oxacalix[4]arenes. Issue 20 (8th May 2019) - Ma, Jiao-Xia; Fang, Xu; Xue, Min; Yang, Yong
Abstract : Oxacalix[4]arenes obtained from the highly efficient, one-pot SN Ar reaction were post-macrocyclization functionalized through the reduction of nitro groups and hydrolysis of the ester groups to obtain several derivatives of desired solubility and anion binding property. Abstract : Oxacalix[4]arenes obtained from the highly efficient, one-pot SN Ar reaction were post-macrocyclization functionalized through the reduction of nitro groups and hydrolysis of the ester groups to obtain several derivatives of desired solubility. The difficulties in basic hydrolysis of ester groups were overcome via developing an acid hydrolysis method for tert -butyl ester derivatives of this class. The synthesis of symmetrical oxacalix[4]arenes from an unsymmetrically substituted precursor was also explored via a multiple step fragment coupling approach. Compounds17 &18 adopted 1, 3-alternate conformations in the solid state as most oxacalix[4]arenes did, and a chair (zigzag) conformation was revealed for tetraamido oxacalix[4]arene (6a ) by X-ray single crystal analysis. The tetraureido oxacalixarene (7 ) showed strong association towards various anions such as F −, Cl −, Br −, I −, Ac −, and HSO4 − with a 1 : 1 stoichiometry as revealed by 1 H NMR analysis and UV-vis measurements.